Self-relevant threat contexts enhance early processing of fear-conditioned faces - Münch, Hannah (Biological psychology, 2016)
Anxiety states are characterized by attentional biases to threat and increased early brain responses to potentially threat signaling stimuli. How such stimuli are processed further depends on prior learning experiences (e.g. conditioning and extinction) and the context in which a stimulus appears. Whether context information and prior learning experiences interact with early threat processing in humans is largely unknown. Here, EEG was recorded while healthy participants (N=20) viewed faces that were fear-conditioned and/or extinguished 24h before. Faces were either passively viewed or presented within different contexts, which were created by describing scenarios that could either involve participants directly (self-threatening), or made them observers (other-threatening) of a potentially dangerous situation. Early brain responses (i.e., P1 amplitudes) were specifically enhanced during the self-threatening condition in response to non-extinguished versus extinguished fear-conditioned faces. This finding suggests that top-down contextual information is incorporated into early attention modulation of previously learned threat signals.